A nano-carbon electrode optimized for adsorptive stripping voltammetry: Application to detection of the stimulant selegiline in authentic saliva - Dos Santos, W; Amin, H; Compton, R (Elsevier, 2018)
A multilayer Carbon Black (CB) modified Glassy Carbon Electrode (GCE) is proposed, developed and optimized for Adsorptive Stripping Voltammetry (AdSV). The thick (up to 1000 monolayers) multilayer CB modification offers a significant enhancement in sensitivity for AdSV but not diffusive voltammetry. The detection of the stimulant selegiline, which is a prohibited drug for athletes in sports competitions, is used as model for application of the proposed electrochemical method in saliva samples. The analytical performance of the CB-GCE for detection of seligeline in authentic saliva samples revealed a limit of detection of 0.12 μmol L−1 which is sufficiently low to allow a possible application of this fast method in the doping control of this drug.